Energy Consumption in Wireless Sensor Networks using Improved K-Means - Anusha, S; Dileep Kumar Reddy, P (International Journal of Computer Sciences and Engineering, 2025)
Remote systems are a developing innovation that will enable clients to get data and from anywhere. The introduce of multi-bounce transmission in remote systems is the arrangement of moderate hubs to hand-off parcels from the source to the goal, in situations where the coordinate correspondence isn't conceivable because of energy or obstruction confinements. In remote correspondence mastermind, it is basic to find the elevated utility course in multi-hop remote frameworks. For this there are immense traditions has proposed for multi ricochet remote frameworks. However, a key issue with existing remote controlling traditions is that restricting the general number of transmissions to pass on a singular package from a source center point to an objective center point that does not have any stretch of the imagination intensifies in the conclusion to-end throughput. We have proposed a new technique for cluster head replacement, which uses improved k-means algorithm. The experimental result shows that the proposed technique gives us better results than existing techniques